A Cause for Celebration: JASM Indexed in Scopus - Marshall J Magnusen; Lawrence W Judge; Jun Kim (Journal of Applied Sports Management, 2025)
The Journal of Applied Sport Management (JASM) achieved a major milestone in Fall 2025 with its acceptance for indexing in Scopus, marking a pivotal advancement in the journal’s visibility, credibility, and global reach. This accomplishment reflects years of collaborative effort among JASM’s editors, reviewers, authors, and the Tennessee Research and Creative Exchange (TRACE) team at the University of Tennessee–Knoxville. Since its founding in 2009 as the Journal of Sport Administration and Supervision and subsequent rebranding in 2013, JASM has evolved into a leading open-access platform for applied sport management scholarship. Under the leadership of Dr. Marshall Magnusen (2020–2025), the journal realized its long-term goal of Scopus indexing, supported by the contributions of associate and assistant editors including Drs. Brooke Forester, Jun Kim, and Lawrence W. Judge. Beginning in 2026, Dr. Judge will assume the role of Editor, continuing to strengthen JASM’s scholarly impact and international influence. With no author fees or access restrictions, JASM remains committed to advancing inclusive, evidence-based research that bridges theory and practice, positioning the journal among the foremost outlets in the field of sport management.
Keywords: award; editor; impact factor; professional association; sport management